BMC Control-M 7 A Journey from Traditional Batch Scheduling to Workload Automation. - Ding, Qiang (Packt Pub., 2012)
Master one of the world?s most powerful enterprise workload automation tools? BMC Control-M 7 - using this book and eBook.